A Social Identity Approach to Engaging Christians in the Issue of Climate Change. Issue 4 (August 2019) - Goldberg, Matthew H.; Gustafson, Abel; Ballew, Matthew T.; Rosenthal, Seth A.; Leiserowitz, Anthony
Using two nationally representative surveys (total N = 2, 544) and two experiments (total N = 1, 620), we investigate a social identity approach to engaging Christians in the issue of climate change. Results show Christian Americans say "protecting God's creation" is a top reason for wanting to reduce global warming. An exploratory experiment and a preregistered replication tested a "stewardship frame" message with Christian Americans and found significant increases in pro-environmental and climate change beliefs, which were explained by increases in viewing environmental protection as a moral and religious issue, and perceptions that other Christians care about environmental protection.